The Narrator in George Eliot’s Fiction: Connections to Modernism - Dallel CHENNI (Revue des Sciences Humaines)
This article attempts to explore and identify literary connections between Victorian fiction as written and developed by George Eliot and Anglo-Saxon modernist literature of the first half of the twentieth century. It highlights the main similarities between Eliot’s intentions as a novelist and what the modernists intended their fiction to achieve. The article discusses  the intentional distinction between the author and the narrator, the characteristic of the latter known as unreliability, the interpretative tasks attributed to the reader, and the author’s interest in both humanism and psychic life as common features between Eliotian and modernist fictions.